UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA TENTANG PENGUKURAN LUAS SEGITIGA MELALUI PENDEKATAN MASTERY LEARNING (BELAJAR TUNTAS) PADA SISWA YANG MENGALAMI STUNTING KELAS IV SDN CIPINANG BESAR SELATAN 15 PAGI - Herlambang, Guido; Faiz Alkhoiri, Muhammad; Sukmawati , Wati; Fitria , Gina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
To improve mathematics learning outcomes regarding measuring the area of ​​triangles through a mastery learning approach (complete learning) for students who experience stunting. The research method used is Classroom Action Research (PTK) with four stages: planning, action, observation and reflection. The research was conducted in class IV of SDN Cipinang Besar Selatan 15 Pagi in the even semester of the 2023/2024 academic year. The research results show that implementing a mastery learning approach can significantly improve student learning outcomes. In the first cycle, the percentage of students who achieved learning completion increased from 40% to 65%. In the second cycle, this percentage increased further until it reached 85%. Discussion of the research results revealed that the mastery learning approach provides an opportunity for students to master the material thoroughly before moving on to the next material, thereby helping students who experience stunting to catch up on their learning. The conclusion of this research is that the mastery learning approach is effective in improving mathematics learning outcomes for students who experience stunting.